High‐sensitivity synchronous image encryption based on improved one‐dimensional compound sine map. Issue 10 (2nd May 2021) - Wang, Xingyuan; Zhang, Maozhen
Abstract: An improved one‐dimensional compound sine map is introduced. The evaluation of this chaotic system shows that it has high sensitivity and random chaotic behaviour. Based on this chaotic system, a new fast image encryption scheme is proposed. Through the cross‐processing of multiple chaotic sequences, two high‐sensitivity pseudo‐random sequences are generated, and the generated high‐sensitivity random sequence is used for synchronization cross‐processing in four directions. Using the symmetry of the image, the image is divided into four directions, and the processing of each direction is different based on the high‐sensitivity sequence and the chaotic value. Through one traversal, the entire image is processed four times differently. The encryption process is uncontrollable and invisible depending on the chaotic sequence. Simulation test results show that the algorithm has good encryption results, is sensitive to the initial secret key and provides satisfactory security capabilities compared with other algorithms.